A fault detection and diagnosis technique for multivariate processes using a PLS-decomposition of the measurement space - Vega, Jorge Ruben (2013)
A newstatisticalmonitoring technique based on partial least squares (PLS) is proposed for fault detection and di- 24 agnosis inmultivariate processes that exhibit collinearmeasurements. A typical PLS regression (PLSR)modeling 25 strategy is first extended by adding the projections of the model outputs to the latent space. Then, a PLS- 26 decomposition of the measurements into four terms that belongs to four different subspaces is derived. In 27 Q2 order to online monitor the PLS-projections in each subspace, new specific statistics with non-overlapped do- 28 mains are combined into a single index able to detect process anomalies. To reach a complete diagnosis, a further 29 decomposition of each statistic was defined as a sum of variable contributions. By adequately processing all this 30 information, the technique is able to: i) detect an anomaly through a single combined index, ii) diagnose the 31 anomaly class from the observed pattern of the four component statistics with respect to their respective confi- 32 dence intervals, and iii) identify the disturbed variables based on the analysis of themain variable contributions 33 to each of the four subspaces. The effectiveness observed in the simulated examples suggests the potential appli- 34 cation of this technique to real production systems.